Pemanfaatan Cerita Rakyat dalam Keterampilan Berbahasa - Merdiyatna, Yang Yang (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2022)
This research is motivated by the desire of researchers to utilize the results of studying folklore in learning language skills. The researcher aims to utilize the results of the study of folklore as an alternative to folklore, thereby adding to the treasures of students' folklore. Students also have additional value from various folklore. The theoretical studies used include matters of culture and learning Indonesian language and literature. The research method used is a pre-experimental design. Students are given learning treatment with the results of folklore studies, then given a test. The results of utilizing the results of folklore studies show good results. Students are enthusiastic in the learning process. The test results also showed that students mastered the material being taught. Thus, the results of the study of folklore have benefits in learning language skills of students. AbstrakPenelitian ini dilatarbelakangi keinginan peneliti untuk memanfaatkan hasil kajian cerita rakyat dalam pembelajaran keterampilan berbahasa. Peneliti bertujuan untuk memanfaatkan hasil kajian cerita rakyat sebagai salah satu alternatif cerita rakyat, sehingga menambah khazanah cerita rakyat peserta didik. Peserta didik pun memiliki tambahan nilai dari beragam cerita rakyat. Kajian teoretis yang digunakan di antaranya adalah perihal kebudayaan dan pembelajaran bahasa dan sastra Indonesia. Metode penelitian yang digunakan adalah rancangan praeksperimental. Peserta didik diberikan perlakuan pembelajaran dengan hasil kajian cerita rakyat, lalu diberikan tes. Hasil pemanfaatan hasil kajian cerita rakyat menunjukkan hasil yang baik. Peserta didik antusias dalam proses pembelajaran. Hasil tes pun menunjukkan peserta didik menguasai materi yang diajarkan. Dengan demikian, hasil kajian cerita rakyat memiliki kebermanfaatan dalam pembelajaran keterampilan berbahasa peserta didik.